IDENTIFICATION OF CHEMICAL COMPOUNDS FROM THE SIMPLISIA OF JACKFRUIT LEAVES (Artocarpus Heterophyllus) USING REAGENTS - Sri Yunita K. Bungi (LP2M Universitas Bina Mandiri Gorontalo, 2022)
The utilization of biodiversity is very large, about 80% of people, especially in developing countries still rely on plants as medicinal ingredients to maintain their health.Jackfruit plants have been known empirically efficacy both on the leaves, fruit, fruit seeds, sap, and wood. Jackfruit leaves can be used as a launching of breast milk, ulcers (external medicine) and wounds, the leaves of this plant are also recommended by Ayurvedic medicine as an antidiabetic remedy. This study aims to identify secondary metabolite compounds in jackfruit leaf simplisia(Aheterophyllus rtocarpus). The group of compounds was tested using reagents to determine the chemical content in the simplisia of jackfruit leaves in the form of lignin, flavonoids and saponin tests. The method of research conducted in this study is the method of experimentation. An experiment is an experiment to prove a particular question or hypothesis. Experiments can be at laboratorium or outside the laboratory, experimental work contains the meaning of learning to do, because it can be incorporated into the learning method. The purpose of the experimental method is that students are able to design, prepare, implement and report experiments. The results showed that in simplisia jackfruit leaves positively contain lignin by using floroglusin LP reagents in addition to jackfruit leaf lignin also positively contains flavonoids using HCL reagents.